The Possible Protective Role of Amygdaline Against Carbon Tetrachloride (CCL4) Induce Certain Biochemical and Antioxidant Changes in Albino Mice (MDA) - Alwan, Iqbal Fadel; Ahmood, Ammar Mawla (Al-Nahrain Journal of Science, 2019)
The study aims to evaluated the protective effect of Amygdaline compound extracted from apricot seeds on the effectiveness of liver enzymes (ALT, AST, GGT) (alkaline phosphatase (ALP), blirubin) cholesterol and triglycerides and(antioxidant (manol dia aldehid MDA), (glotathuine-S- transters (GST)) on the albino mice treated with carbon tetrachloride were studied 32 male albino mice Swiss albino, (5-8 weeks) and (20-25 gm weight).Amygdaline compound was analyzed by High-performance liquid chromatography technique (HPLC). Conducted tests on the overlap between the three concentration ( 150, 250,350 mg/kgm) of aqueous extract of Amygdaline 3.2 mg/kgm of carbon tetrachloride with interaction included two types of treatment (pre-ccl4 and post-ccl4) through oral dosage and for a period of 14 days. The study shows that the concentration 350 mg/kgm is the best concentration of aqueous extract there was used and study suggests that use the concentrations of this focus and fact that the plant is used for human consumption broadly and because it contains the Bio flvenote.